2012
DOI: 10.1159/000339407
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Responsive Nephrotic Syndrome and Bilateral Renal Artery Stenosis: A Possible Role for Angiotensin-Mediated Podocyte Injury

Abstract: Nephrotic syndrome (NS) associated with renal artery stenosis is not widely recognized or investigated as a cause of the NS. The mechanisms are incompletely understood, but have largely focused on hemodynamic factors resulting in hyperfiltration injury-induced focal and segmental glomerulosclerosis (FSGS) in the nonstenosed kidney with sparing of the stenotic kidney protected from hemodynamic stress. However, separation of hemodynamic from circulating factors (such as angiotensin II) as the cause of the nephro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Proteinuria dramatically improves following medical therapy or revascularization in most cases. However, Bhardwaj et al suggested that immune-mediated injury, not a hemodynamic factor, is involved in development of this condition and reported that NS resolves after steroid therapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria dramatically improves following medical therapy or revascularization in most cases. However, Bhardwaj et al suggested that immune-mediated injury, not a hemodynamic factor, is involved in development of this condition and reported that NS resolves after steroid therapy [13].…”
Section: Discussionmentioning
confidence: 99%